100 illustrators - Heller, Steven, 1950-; Wiedemann, Julius (Bibliotheca Universalis (Taschen), 2021)
"Fine lines 100 illustrators to remember drawn from TASCHEN's Illustration Now! series, this go-to catalog brings together 100 of the most successful and important illustrators around the globe. With featured artists including Istvan Banyai, Gary Baseman, Seymour Chwast, Paul Davis, Brad Holland, Mirko Ili, Anita Kunz, and Christoph Niemann, the international overview provides an invigorating record of the dynamism and diversity of the illustration scene. Each illustrator is featured with a self-portrait, samples from their portfolio, and a succinct description by Steven Heller, with a supplementary list of selected exhibitions and publications. In his introduction, Steven Heller describes the dynamic realm of illustration today and the challenging process of selection within this highly competitive and ever-moving genre."- Resumé vydavatel